Avaliação da reação em cadeia da polimerase para identificação do complexo Mycobacterium tuberculosis em cultura de escarro no meio BACTEC 12B - Gouveia, Ana Cláudia Carvalho (2006)
Use of the most rapid and reliable laboratory tests for Mycobacterium tuberculosis detection and identification is important for tuberculosis (TB) control. Diagnostic techniques based on molecular biology methods are able to dramatically reduce the time of detection as well as increase the sensitivity for detecting the bacilli. A polymerase chain reaction DNA amplification method for direct detection of Mycobacterium tuberculosis Complex (PCR IS6110) in BACTEC 12B broth cultures was evaluated. A total of 107 sputum samples were processed by standard methods, and then inoculated into Ogawa slants and BACTEC 12B vials. The PCR assay was used on BACTEC 12B broth cultures with a growth index (GI) of equal to or greater than 30. Molecular results were compared to those obtained by phenotypic identification methods. Of the 107 broth cultures evaluated, 90 were all culture and PCR positive for M. tuberculosis. Except for one, all cultures (n = 8) which grew mycobacteria other than M. tuberculosis were PCR negative. In two cultures which grew both mycobacteria and other organisms than acid-fast bacilli a phenotypic identification was not possible, and both of them were PCR negative. The remaining seven cultures that did not contain mycobacteria were PCR negative. Of particular interest were all 44 cultures positive from smear-negative sputum specimens and three contaminated BACTEC 12B broth cultures yielding mycobacterial growth which a M. tuberculosis Complex, which were successfully identified by PCR, resulting in a mean time to identify M. tuberculosis of 5,5 and 16 days before phenotypic identification, respectively. In light of an overall sensitivity and specificity of 100% and 87,5%, respectively, coupled with the ability to identify the bacilli days or weeks before other methods can be applied, we conclude that PCR might prove to be a rapid alternative for identification of M. tuberculosis Complex in culture, even in the context of paucibacillary patients.